On spectral gaps of the Hill—Schrödinger operator with singular potential - Mikhailets, V.A.; Molyboga, V.M. (Reports of the National Academy of Sciences of Ukraine, 2018)
We study the continuous spectrum of the Hill—Schrödinger operator in a Hilbert space L2(R). The operator potential belongs to a Sobolev space Hloc−1(R). The conditions are found for the sequence of lengths of spectral gaps to: a) be bounded; b) converge to zero. The case where the potential is a real Radon measure on R is studied separately.